ASSESSING ENGLISH STUDENTS’ DIGITAL LITERACY IN WRITING THESIS - Sulistiawati, Ayuni; Dr. Yelfiza, M.Pd,; Siska, S.S, M.Pd, (Jurnal Teknologi Pendidikan, 2024)
This study aims to determine the digital literacy competence of students in using digital tools that focus on ChatGPT and Mendeley in writing a thesis at PGRI University of West Sumatra as seen from three components: information literacy, media literacy, and ICT literacy. This type of research is a mixed method with descriptive analysis. This research focuses on collecting data from 7 English students enrolled in 2020. In the data collection, interviews and rubrics were used to obtain data on students' digital literacy. The data collected were analyzed qualitatively (interviews) and quantitatively (rubrics) using Excel calculations. The results showed that students' digital literacy towards ChatGPT and Mendeley was categorized as good but in the good category which was still at a low level based on the three components of digital literacy. Based on these results, although categorized as good, there are times when students can improve their digital literacy to an excellent category. Based on this condition, educational institutions should integrate digital literacy as a core component in their training programs, by including specific courses on information, media and ICT literacy. Keywords: ChatGPT, Digital Literacy, Digital Tools, Mendeley, Thesis Writing.